Integrating Civic Engagement to Foster Soft Skills and Teacher Professionalism - Hodriani; Pinem, Windawati; Sutrisno; Safitri, Ira; Bahauddin, Nur Ain binti (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) program, launched in 2019, provides students opportunities to strengthen their professional competencies through direct engagement in the real world. Within this framework, civic engagement is essential, as it encourages students to actively participate in community-based activities that support their academics and social responsibilities. This study analyzes how students develop soft skills and teaching professionalism through MBKM activities. This qualitative descriptive study involved students of the Pancasila and Citizenship Education Department at Medan State University, class of 2019–2021, who had participated in MBKM programs such as Kampus Mengajar (Teaching Campus), student exchange programs, and internships. Data were collected through interviews, observations, and documentation, then analyzed using an interactive model. The research findings indicate that civic engagement integrated into MBKM improves adaptability, leadership, communication, collaboration, and innovation, while instilling civic values and professional ethics. This study recommends systematically institutionalizing civic engagement in teacher education curricula to ensure holistic and sustainable outcomes.